2012
DOI: 10.1007/s00125-012-2570-9
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation end-products (AGEs) and functionality of reverse cholesterol transport in patients with type 2 diabetes and in mouse models

Abstract: Aims/hypothesis We investigated the contribution of AGEs to the impairment of reverse cholesterol transport (RCT) variables in diabetic individuals and in two animal models of diabetic obesity and of renal impairment. Methods The capacity of plasma and HDL from 26 individuals with moderately controlled type 2 diabetes to support cholesterol efflux was compared with 26 age-and sexmatched individuals without diabetes. We also compared the rates of RCT in vivo in two animal models: db/db mice and mice with chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 48 publications
1
38
2
1
Order By: Relevance
“…Nevertheless, we (Kralova Lesna et al, 2008) and others (Fadini et al, 2014;Low et al, 2012) have clearly shown that HDL cholesterol and ApoA1 concentrations do not necessarily correspond to the real capacity of RCT. Therefore, we included the direct determination of plasma-induced cholesterol efflux from human macrophages as an RCT measure.…”
Section: Introductionmentioning
confidence: 78%
“…Nevertheless, we (Kralova Lesna et al, 2008) and others (Fadini et al, 2014;Low et al, 2012) have clearly shown that HDL cholesterol and ApoA1 concentrations do not necessarily correspond to the real capacity of RCT. Therefore, we included the direct determination of plasma-induced cholesterol efflux from human macrophages as an RCT measure.…”
Section: Introductionmentioning
confidence: 78%
“…38, 184 In a recent study, HDL and sera of diabetic subjects were found to display increased rather than decreased cholesterol efflux capacity, which correlated with CETP activity but not with AGE levels. 191 Neither showed AGE levels any association with macrophage reverse cholesterol transport in vivo of db/db mice or uremic mice. 191 HDLs enriched with either AGE in T2DM patients or with MDA in CAD patients failed to inhibit monocyte or neutrophil diapedesis through endothelial cells by suppressing VCAM-1 and intracellular adhesion molecule-1 expression.…”
Section: Hdl Dysfunctionmentioning
confidence: 91%
“…191 Neither showed AGE levels any association with macrophage reverse cholesterol transport in vivo of db/db mice or uremic mice. 191 HDLs enriched with either AGE in T2DM patients or with MDA in CAD patients failed to inhibit monocyte or neutrophil diapedesis through endothelial cells by suppressing VCAM-1 and intracellular adhesion molecule-1 expression. 38,192 Both the HDL of CAD patients and that of healthy subjects enriched with MDA bind to the scavenger receptor LOX-1 of endothelial cells.…”
Section: Hdl Dysfunctionmentioning
confidence: 91%
“…13,14 In one small study, CEC to apoB-depleted plasma moderately correlated with CEC to isolated HDL (r=0.46, p<0.02) but was not correlated at all with CEC to whole plasma (p>0.2). 15 Ascertaining the specific methodology used to assess CEC is critical when evaluating the reported findings in human studies. Correlations between CEC and other lipid markers can vary widely whether using whole vs. apoB-depleted plasma/serum as the cholesterol acceptor.…”
Section: Measuring Cholesterol Efflux Capacity (Cec) In Humansmentioning
confidence: 99%